Mechanical characterization of aluminium alloy LM25 reinforced with TiC and graphite for structural applications. (2023) - Velavan, K.; Palanikumar, K.; Thirumal, K.; Ragul Kannan, K.; Kannan, M.; Arunkumar, P.
Highlights: A novel hybrid aluminium metal matrix composite was fabricated through economic stir casting route . Mechanical strength increases with higher reinforcement of TiC particles. Wear resistivity increases with addition of TiC and graphite addition lowers the CoF. Uniform distribution of TiC and graphite provides better strength. Abstract: Aluminium and its alloys are most promising materials in automobile, electronic and aviation industries. But their usage is limited because of lower strength and lower resistance towards wear and harsh environment subjected to heavy temperatures and load. Hence to improve its strength and wear resistance, ceramic particulates are to be reinforced in definite weight fractions. Similarly, to improve its wear resistance, solid lubricants too should be added. Based on this titanium carbide (TiC) ceramic particles of 0, 3, 6 and 9 wt% are reinforced in the matrix of LM25 alloy along with hybrid reinforcement of 3% graphite (Gr). Aluminium hybrid metal matrix composites (AHMMCs) are manufactured using the liquid processing approach, and their material properties, such as tensile and impact strength, and hardness, are assessed in accordance with ASTM criteria. The dispersal of particulates in aluminium matrix is visualized using optical micrographs and it is seen that uniform distribution is achieved with stir casting. It is observed from mechanical properties that with inclusion of ceramic reinforcements, tensile, impact and hardness values tend to increase. Wear studies performed on pin-on-disc (PoD) shows that with inclusion of ceramic and graphite particles lower wear loss is achieved against the unreinforced LM25 alloy.